Evaluation of digital games for autistic children using heuristics and observation tests - Silva, Adhonay Júnior; Romeiro, Tiza Verciano; Nobre, Cristiane Neri (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Autism is a neurological disorder characterized by the impairment of social interaction, verbal and nonverbal communication, and restricted and repetitive behavior, which can be treated with specialized therapies, according to each case. With the use of digital games, making these therapies more assertive, the disorder’s effects are minimized over time. Considering the game’s potential in this context, this work raised heuristics that can assist in the development and evaluation of these games. These heuristics tend to make the creation more assertive in the development stages, creating a better user experience. Besides, Aiello and TEO-Autism games were evaluated for tests of interaction and observation with autistic users. The results point to a good acceptance of the games evaluated and reinforce the heuristics previously raised.